Determination of Long-Term (1993–2019) Sea Level Rise Trends Around the Korean Peninsula Using Ocean Tide-Corrected, Multi-Mission Satellite Altimetry Data - Lee, KyungJae; Nam, SungHyun; Cho, Yang-Ki; Jeong, Kwang-Young; Byun, Do-Seong (Frontiers in Marine Science, 2022)
It is vital to improve estimations of long-term trends in global and regional sea level rise to help mitigate and adapt to climate change. Satellite altimetry data have been widely used for this purpose; however, data collected in regions with strong tidal motions often suffer from significant aliasing effects unless they are sufficiently corrected using accurate ocean tide models. Long-term trends estimated from altimetry data are often also considerably affected by regional circulation changes, and by artificial effects arising from inconsistencies between different satellite missions. Here, we focused on two regions with high (>5 mm·yr-1) rates of long-term linear trend in sea level rise (LTSLR) around the Korean Peninsula (KP). We addressed the impacts of tidal correction and mission inconsistency in satellite altimetry data, and discussed the potential impacts of circulation changes on LTSLR. Because the LTSLR estimation is affected by the aliasing effects of altimetry data when the tidal motions are not corrected sufficiently, yet the correction depends on the performance of ocean tide models, we employed eight ocean tide models to correct altimetry data for comparison and validated the results against observations from 13 tide gauge (TG) stations around the KP. We also estimated LTSLR from 1993 to 2019 using annual mean sea level anomalies (SLAs) from two satellite (two-sat) and all 21 satellite (all-sat) missions, with corrections for ocean tides. The TPXO9 model showed the most reasonable spatial LTSLR rate pattern (~3 mm·yr-1), with the smallest difference from TG observations. It performed best near the west coast where the tidal range was the largest and when using two-sat data, because of inconsistencies in all-sat altimetry data. In contrast, off the east coast, where the impact of tidal correction is negligible, the high (~7 mm·yr-1) LTSLR rates were robust regardless of ocean tide models and altimetry missions, potentially driven by long-term changes in regional circulation. Our results highlight the importance of tidal correction and mission inconsistency for improving LTSLR estimations around the KP. They also have significant implications for determining regional sea level rise under changing circulation patterns, within and beyond the region.